PENGARUH PENGGUNAAN BUKU CERITA BERGAMBAR TERHADAP LITERASI MEMBACA SISWA TINGKAT SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the extent to which picture books can influence students' reading literacy skills at the elementary school level, as well as to examine the role of family support in increasing children's interest in reading. Reading literacy is a core skill that determines student learning success. However, many students still experience difficulties in understanding the content of what they read, identifying main ideas, and summarizing information. Picture books have proven to be an effective tool because they combine text with attractive illustrations, thereby stimulating interest, sharpening understanding, and enriching students' vocabulary. This study adopted a triangulation method through observation, interviews, and documentation. Observations were conducted to see students' interactions with picture books, interviews with teachers and parents were used to determine the development of reading interest, while documentation complemented the data. The findings showed that picture storybooks had a significant effect on improving reading literacy. Students became more enthusiastic, more focused, and found it easier to understand the storyline with the help of illustrations. Reading motivation also increased both at school and at home. Parents reported that their children began to ask for more time to read together. Overall, picture storybooks were proven to improve reading skills, enrich vocabulary, and encourage reading habits.